Nano-reinforcement effect on PMMA denture base mechanical properties after immersing in different solution - Hussein, Samah M.; Rasheed, Zaynab N. (Iraqi Journal of Science, 2019)
Poly methyl methacrylate PMMA polymer has been used continually in dental application during the recent years. Yet, it is commonly known for its poor strength properties for long periods under pressure. The aim of this research was to improve the performance of PMMA denture base through the addition of different nanoparticles selected from artificial and natural sources. For comparison, Nano -particles from Al2O3 and crushed pistachio shell were utilised. (1%, 2% and 3%) were the weight fraction used in this study for both reinforcement types. In this work, a study and evaluation in of Compression Strength (C.S.) as well as Young’s Modulus (Y) was done before and after exposure for special liquids. The new prepared composites were immersed in two type of liquids (vinegar and olive oil). Both physical values were determined periodically for three specific times (10, 20 and 30 min).All tests were carried out at room temperature. As a result a clear increase was obtained in the evaluated values of (C.S.) and Young’s Modulus for the composite samples after the addition of both type of particles compared to the pure case. As the weight fraction was increased, these values also increased. It was found that the pure polymer (PMMA) lost almost half of the value of C.S. after 30 min of exposure in both liquid used. When immersing the prepared composites inside both liquids While the obtained results for pistachio shells particles showed slight increase after 10 min of exposure then a slight decrease through the time. Overall, the prepared composites for both type particles showed a better behavior after immersion in these liquids than the pure PMMA polymer. Also, a significant enhancement was clear with the determined value of Young’s Modulus between the prepared composites compared to the non-reinforced PMMA in all situations.